The Influence of Learning Media on Student Activity: Bahasa Indonesia - Kencono, Melati Retno; Ratnasari, Eka (Buana Pendidikan, 2021)
In the era of 4.0 where technology is increasingly clothing and developing, it is easier for an educator to find information and float learning media. An educator is required to be able to keep up with the times. Technology is increasingly sophisticated and changing, but there are still many educators who have not been able to develop learning media. Learning media has a big influence on the activity of students in the classroom for the material conveyed by the teacher. Attractive learning media will make students easily accept the material presented by the teacher and appropriate learning media will make children not easily bored during learning activities. For this reason, the teacher determines the appropriate learning media for students. By choosing the right learning media, it will attract students' interest in learning and be able to make students active in learning.